Studi literatur: Efektivitas weaning ventilasi mekanik dengan pressure support ventilation (PSV) vs T-piece - Sungkono Sungkono; Riri Maria (Holistik Jurnal Kesehatan, 2021)
The effectiveness of mechanical ventilation weaning with pressure support ventilation (PSV) vs T-piece: A Literature studyBackground: Prolonged mechanical ventilation can increase the risk of infection, length of stay in the ICU, length of hospital stay, mortality, and cost of healthcare. The mechanical ventilation weaning process can be done using the pressure support (PSV) method or using a T-Piece. Purpose: Determine the effectiveness of the PSV vs T-Piece method in mechanical ventilation weaning.Method: The literature research uses electronic databases including PubMed, CINAHL, Proquest, and google scholar. Keywords for data search are using the keywords "SBT", "Pressure support", "T-piece", "weaning mechanical ventilation". Inclusion criteria: English-language journal, RCT design, published from 2010 to 2020, and full text.Results: The results were five RCT studies with a total number of respondents as many as 2038 patients. Two studies suggest that both the PSV and the T-piece methods have the same success rate. Three studies stated that there was no difference in the reintubation rate <48 hours, the mortality rate, and the length of the stay in the hospital. The length of stay in the ICU from five studies also suggested no difference.Conclusion: The mechanical ventilation weaning method or SBT with the PSV and T-Piece methods in general there is no difference in the success rate or in the outcomes.Keywords: Weaning Mechanical Ventilation; Effectiveness; PSV T-PiecePendahuluan: Prolong ventilasi mekanik dapat meningkatkan resiko infeksi, lama rawat ICU, lama rawat rumah sakit dan mortalitas serta biaya perawatan. Proses weaning ventilasi mekanik dapat dilakukan dengan metode pressure support (PSV) atau menggunakan T-Piece.Tujuan: Mengetahui efektivitas metode PSV vs T-Piece dalam weaning ventilasi mekanik.Metode: Pencarian literature menggunakan database elektronik termasuk didalamnya PubMed, CINAHL, Proquest dan google scholar. Kata kunci pencarian data yaitu dengan menggunakan kata kunci “SBT”, “Pressure support”, “T-piece”, “weaning mechanical ventilation”. kriteri inklusi: jurnal berbahasa inggris, desain RCT, dipublikasikan dari tahun 2010 sampai dengan 2020, dan full text.Hasil: Ada lima Studi RCT dengan Total jumlah reponden sebanyak 2038 pasien. Dua studi menyatakan bahwa baik metode PSV dan T-piece mempunyai tingkat keberhasilan yang sama. Dari tiga studi menyatakan bahwa angka kejadian reintubasi < 48 jam tidak ada perbedaan, angka mortalitas dan lama rawat ICU dari lima studi tidak ada perbedaan. Dari tiga studi lama rawat di rumah sakit tidak ada perbedaan.Simpulan: Metode weaning ventilasi mekanik atau SBT dengan metode PSV dan T-Piece secara umum tidak ada perbedaan dalam tingkat keberhasilan maupun dalam outcomenya.